In Vivo Time-Course Imaging of Tumor Angiogenesis in Colorectal Liver Metastases in the Same Living Mice Using Two-Photon Laser Scanning Microscopy. (3rd November 2011) - Tanaka, Koji; Morimoto, Yuhki; Toiyama, Yuji; Matsushita, Kohei; Kawamura, Mikio; Koike, Yuhki; Okugawa, Yoshinaga; Inoue, Yasuhiro; Uchida, Keiichi; Araki, Toshimitsu; Mizoguchi, Akira; Kusunoki, Masato
Abstract : In vivo real-time visualization of the process of angiogenesis in secondary tumors in the same living animals presents a major challenge in metastasis research. We developed a technique for intravital imaging of colorectal liver metastasis development in live mice using two-photon laser scanning microscopy (TPLSM). We also developed time-series TPLSM in which intravital TPLSM procedures were performed several times over periods of days to months. Red fluorescent protein-expressing colorectal cancer cells were inoculated into the spleens of green fluorescent protein-expressing mice. First- and second-round intravital TPLSM allowed visualization of viable cancer cells (red) in hepatic sinusoids or the space of Disse. Third-round intravital TPLSM demonstrated liver metastatic colonies consisting of viable cancer cells and surrounding stroma with tumor vessels (green). In vivo time-course imaging of tumor angiogenesis in the same living mice using time-series TPLSM could be an ideal tool for antiangiogenic drug evaluation, reducing the effects of interindividual variation.